2021
DOI: 10.3390/buildings11120621
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of LSF Wall Systems with Vacuum Insulation Panels

Abstract: Lightweight Steel Frames (LSF) in building construction are becoming more popular due to their fast, clean, and flexible constructability. Typical LSF wall panels are made of cold-formed and thin-walled steel lipped channel studs with plasterboard linings. Due to the high thermal conductivity of steel, these LSF components must be well engineered and covered against unintended thermal bridges. Therefore, it is essential to investigate the heat transfer of the LSF wall of different configurations and reduce hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Thus, an alternative can be the use of nano-insulation materials, also called super insulation materials (SIM), that are defined by a remarkable reduced thermal conductivity (e.g., a thermal conductivity around 15 mW/(m•K) or even lower). As it was demonstrated by Rajanayagam et al in [15], when using SIMs the same thermal performance will be reached at lower thicknesses compared to conventional thermal insulation materials thicknesses. The paper also demonstrated that the implemented SIM solution was able to reach the imposed building requirements and help address solutions that can be defined by constructive constraints.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Thus, an alternative can be the use of nano-insulation materials, also called super insulation materials (SIM), that are defined by a remarkable reduced thermal conductivity (e.g., a thermal conductivity around 15 mW/(m•K) or even lower). As it was demonstrated by Rajanayagam et al in [15], when using SIMs the same thermal performance will be reached at lower thicknesses compared to conventional thermal insulation materials thicknesses. The paper also demonstrated that the implemented SIM solution was able to reach the imposed building requirements and help address solutions that can be defined by constructive constraints.…”
Section: Introductionmentioning
confidence: 68%
“…In the case of LSF constructions placed in cold-dominated climates, the need for an accurate design becomes even more critical. Although the number of LSF buildings is increasing around the globe [13,14] due to their advantages compared to heavyweight constructions, the high thermal conductivity of steel elements may lead to significant thermal bridges, which must be well tackled at the design stage to decrease their negative impact on the energy demand for space heating and cooling [15]. Compared to conventional constructive details, the poor thermal performance of the steel elements can be offset by employing adequate thermal insulation solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 Developed and validated 2D and 3D geometry ABAQUS models and applied boundary conditions [1].…”
Section: Fe Model Development and Validationmentioning
confidence: 99%
“…Since buildings are responsible for 40% of Europe's energy consumption and 36% of the continent's carbon dioxide emissions, transforming them to be more energy efficient and developing novel technical systems to improve their energy performance is crucial [1][2][3]. In the Energy Performance Building Directive, the European Union (EU) set certain goals for the year 2020, which includes "nearly zero-energy buildings" [1][2][3][4][5]. In general, operational energy (the energy required to run the structure's operations) far surpasses the embodied energy (the energy required to manufacture the building's individual features) throughout the course of a building's lifecycle.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the increase in the number of studs and the thickness of the protection layers will enhance the fire performance, and the use of super-wool insulation provides a higher fire resistance than rockwool. Rajanayagam et al [29] have conducted a numerical analysis to investigate the thermal performance of LSF walls and study the effect of novel thermal insulation materials. Rahnavard et al [30] presented a 2D numerical model of heat transfer analysis with the aim of providing a new analytical formulation for the prediction of the temperature evolution within the concrete-filled cold-formed steel section (CF-CFS) when subjected to fire.…”
Section: Introductionmentioning
confidence: 99%